Leos Janacek Kát'a Kabanová - Tyrrell, John (Cambridge Cambridge University Press, 1982)
Kát'a Kabanová is both the first Janácek opera to have been performed in Britain and the one which has received the most productions in Britain and the USA. In this book John Tyrrell brings together letters, early reviews and other documents (most of them translated from Czech for the first time) on the opera's composition and its early performances. A group of key interpretations of the opera ranges from one by the opera's German translator and Janácek's first biographer Max Brod to specially commissioned essays by Wilfrid Mellers and by David Pountney, producer of the highly successful Welsh National Opera/Scottish Opera Janácek cycle.